(untitled) (Cuea Journal of Business and Economics, 2025)
Effective public financial management is critical for good governance and sustainable development. In Kenya, county governments continue to face sustainability challenges due to persistent financial inefficiencies. This study examined the relationship between financial controls and sustainability of county governments in Kenya. The study used a positivist paradigm with an ex-post facto design, the study targeted 23 counties within the LREB, NOREB, and SEKEB economic blocs. A multi-stage sampling technique yielded 1,219 finance staff as respondents. Data were collected through questionnaires and secondary records and analyzed using descriptive statistics and Structural Equation Modeling. The findings indicated that strong financial controls enhanced fund security, efficiency, and plan adherence. The study concludes that county government sustainability relies on strengthening both development and recurrent budget management. It recommends enhancing internal controls, regular audits, staff capacity building, and adoption of digital revenue systems, participatory budgeting, and strategic partnerships. Real-time monitoring and improved interdepartmental coordination are also essential for long-term financial sustainability.